Canons 631 §§1-2 and 632: Regarding the Use of Telecommunications for the Convocation of Collegial or Similar Bodies - Katholische Kirche Kongregation für die Institute des Geweihten Lebens und die Gemeinschaften des Apostolischen Lebens; Bráz de Aviz, João 1947- (2021)
The Covid-19 global pandemic has continued to disrupt the ability of organizational leaders throughout the world to communicate through in-person gatherings. The leaders of various institutes of consecrated life and societies of apostolic life (ICL-SAL) asked for a reconsideration of a 2020 opinion with regard to whether they could hold meetings through electronic means. The response of the Congregation for Institutes of Consecrated Life and Societies of Apostolic Life follows.